Zróżnicowanie przestrzenne i przebieg roczny opadów atmosferycznych w dorzeczu Stobrawy w latach 1954-1980 - Jaskulska, Alicja (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The characteristics of spatial diversity of the annual precipitation distribution in the Stobrawa River basin between 1956 and 1980 is presented in the article. The study was based on average monthly precipitation from 11 precipitation stations located in the research area, as well as from 6 precipitation stations and 1 meteorological station, in Opole, situated outside the basin’s boundaries. The yearly progress of monthly precipitation was the subject of the analysis. Maps of its geographical distribution were drawn, which allowed the areas of the highest and the lowest average monthly precipitation to be indicated, as well as to specify the factors that influence this variation. It was also determined what the maximum and minimum amounts of precipitation in the examined period were.
Keywords: Precipitation; Precipitation variability; Stobrawa River basin